Topics In Contemporary Differential Geometry, Complex Analysis And Mathematical Physics : Proceedings of the 8th International Workshop on Complex Structures and Vector Fields. - Dimiev, Stancho (World Scientific, 2007)
This volume contains the contributions by the participants in the eight of a series workshops in complex analysis, differential geometry and mathematical physics and related areas. Active specialists in mathematical physics contribute to the volume, providing not only significant information for researchers in the area but also interesting mathematics for non-specialists and a broader audience. The contributions treat topics including differential geometry, partial differential equations, integrable systems and mathematical physics.